Assessing Proprioceptive Function: Evaluating Joint Position Matching Methods Against Psychophysical Thresholds. Issue 4 (1st April 2014) - Elangovan, Naveen; Herrmann, Amanda; Konczak, Jürgen
Abstract : Background: The importance of assessing proprioceptive function for rehabilitation after neurological or orthopedic injury has long been recognized. Yet, neither the validity nor the accuracy of the available tests is firmly established. Testing typically involves repeated matching of a given joint position with the same or opposite limb where the difference between the 2 positions indicates proprioceptive acuity. Objectives: The aim of this study was to compare position sense acuity between ipsilateral and contralateral matching methods against a psychophysical threshold method to establish the accuracy and relationships between these models. Design: A repeated-measures design was used. Method: Assessment of forearm position sense for a 10-degree reference position in 27 young adults who were healthy. Results: Psychophysical thresholds were revealed to be the most precise and least variable acuity measure. The mean (±SD) threshold (1.05°±0.47°) was significantly lower than mean position errors obtained by both joint position matching tasks (ipsilateral: 1.51°±0.64°; contralateral: 1.84°±0.73°)—a 44% to 75% difference in measurement accuracy. Individual participant position errors correlated poorly with respective thresholds, indicating a lack of concurrent validity. Position errors for both matching methods correlated only mildly with each other. Limitations: The data represent performance of a healthy, young adult cohort. Differences between methods will likely be more pronounced in aging and clinical populations. Conclusions: Threshold testing and joint position matching methods examine different physiological aspects of proprioceptive function. Because threshold testing is based on passive motion, it most closely reflects afferent sensory feedback processing (ie, proprioception). Matching methods require active motion and are consequently influenced by additional sensorimotor processes. Factors such as working memory and transmission between brain hemispheres also influence joint matching task outcomes.